INOVASI DIGITAL MARKETING PADA ASPEK ¬REBRANDING TEH BUNGA TELANG PRETREATMENT ASAM SEBAGAI UPAYA PENINGKATAN DAYA SAING PRODUK HERBAL - Wijinindyah, Ayutha; Selvia, Jerry; Nurhayati, Novi; Sugama, Muchamad Yoga; Rossayanti, Rossayanti; Hasanah, Laila Uswatun (Universitas Mataram, 2024)
Telang flower tea is one of the plants that has potential as an herbal drink because it can treat several diseases. The partner is a Women Farmers Group that has a telang flower tea production business. One of the obstacles faced is that the marketing aspect is still limited because the product is less attractive and less recognized by the public. The purpose of this activity is to rovide digital marketing education, with the rebranding aspect for acid pretreatment of telang flower. The method of implementing activities is through education with presentation, pre test and post test, Focus Group Discussion (FGD), as wel as hands on activities. The result of this activity is that partners are open to improving product branding, including logo improvements. The conclusion is that digital marketing in the aspect of rebranding is able to increase the competitiveness of herbal products more widely.